Variable gain control scheme of DFIG-based wind farm for over-frequency support. (May 2018) - Li, Yujun; Xu, Zhao; Zhang, Jianliang; Wong, Kit Po
Abstract: In order to mitigate over-frequency events in the power systems, this paper proposes a new variable gain based control strategy to maximize the frequency support while minimizing impacts to the overall energy production for a wind power plant (WPP). Because of different wind conditions, the energy production by each WT is not equally compromised by adaptively adjusting the droop gains according to the different rotor speeds so that minimal reduction of energy production can be ensured. The control performance was fully investigated in a doubly fed induction generator (DFIG) based WPP and the results clearly indicate the proposed variable droop gain scheme can harness more wind energy than the conventional same droop gain scheme while providing similar frequency support. Highlights: We focus the over-frequency disturbances in power systems with high penetration of renewable. Wake interaction model of wind turbines is fully considered. We prove front-row wind turbines may compromise more wind production than those back-row ones. A variable droop gain scheme for a wind farm is proposed for system support. The proposed scheme can harvest as much wind energy as possible while providing system support.